Insight into Stability Analysis on Modified Magnetic Field of ‎Radiative Non-Newtonian Reiner–Philippoff Fluid Model‎ - Iskandar Waini; Abdul Rahman Mohd Kasim; Najiyah Safwa Khashi’ie; Nurul Amira Zainal; Anuar Ishak; Ioan Pop (Journal of Applied and Computational Mechanics, 2022)
The field of magnetohydrodynamics (MHD) encompasses a wide range of physical objects due to their stabilising effects. Thus, this study concerns the numerical investigation of the radiative non-Newtonian fluid flow past a shrinking sheet in the presence of an aligned magnetic field. By adopting proper similarity transformations, the governing partial derivatives of multivariable differential equations are converted to similarity equations of a particular form. The numerical results are obtained by using the bvp4c technique. According to the findings, increases in the suction parameter resulted in higher values of the skin friction and heat transfer rate. The same pattern emerges as the aligned angle and magnetic parameter are considered. On the other hand, the inclusion of the Bingham number, the Reiner–Philippoff fluid, and the thermal radiation parameters deteriorate the heat transfer performance, evidently. The dual solutions are established, which results in a stability analysis that upholds the validity of the first solution.